PERAN DELIK KESUSILAAN DALAM MELINDUNGI MORALITAS DAN NORMA SOSIAL - Nafelita, Chiesa Almeyda (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
The development of modern society has brought significant social changes in various aspects of life. One aspect that has been affected is morality and social norms. Morality and social norms are the ethical foundations that govern individual behavior and social interactions in society. However, with technological advancements and changing social values, there are new challenges in preserving morality and social norms. In this article, the author explores the role of offenses against decency in protecting morality and social norms. Decency encompasses a set of values and principles that regulate sexual behavior and interpersonal relationships. This article employs a normative research method by analyzing theories and relating them to legal norms, which are closely intertwined with legislation and regulations. The results of this analysis state that offenses against decency play an important role in protecting morality and social norms. Through the appropriate application of the law, offenses against decency can help maintain moral values that are considered important in society.